Low-frequency pre-treatment HIV drug resistance: effects on 2-year outcome of first-line efavirenz-based antiretroviral therapy. (15th November 2022) - Milne, Ross S.; Beck, Ingrid A.; Levine, Molly; So, Isaac; Andersen, Nina; Deng, Wenjie; Panpradist, Nuttada; Kingoo, James; Kiptinness, Catherine; Yatich, Nelly; Kiarie, James N.; Sakr, Samah R.; et al.
Abstract : Objective(s): Assess the impact of pre-treatment high-frequency and low-frequency drug-resistant HIV variants on long-term outcomes of first-line efavirenz-based antiretroviral therapy (ART). Design: Prospective observational study. Methods: Participants' pre-treatment plasma RNA had two sections of HIV pol encoding reverse transcriptase sequenced (Illumina, MiSeq) using unique molecular identifiers to detect wild-type (pre-treatment drug-resistant variants less than 1% of viral quasispecies), low-frequency (1–9%) or high-frequency drug-resistant variants (10–100%). Associations between pre-treatment drug resistance and virologic outcomes over 24 months of efavirenz-based ART were assessed for the number and frequency of mutations by drug class and other resistance parameters. Results: Virologic failure was detected in 30 of 352 (9%) and pre-treatment drug-resistant variants were detected in the viral quasispecies of 31 of 352 (9%) participants prescribed efavirenz-based ART. Survival analyses revealed statistically significant associations between pre-treatment drug resistance at low ( P  < 0.0001) and high ( P  < 0.001) frequencies, at oligonucleotide ligation assay (OLA) ( P  < 0.00001) and non-OLA ( P  < 0.01) codons, to a single-antiretroviral class ( P  < 0.00001), and a shorter time to virologic failure of efavirenz-based ART. Regression analyses detected independent effects across resistance categories, including both low-frequency ( P  < 0.01) and high-frequency ( P  < 0.001) drug-resistant variants. Conclusion: We observed that pre-treatment HIV drug resistance detected at low frequencies increased the risk of virologic failure over 24 months of efavirenz-based ART, but that most failures, regardless of drug-resistant variants' frequencies, were detected within a year of ART initiation. These observations suggest that when efavirenz-based ART is prescribed, screening for pre-treatment drug resistance by an assay capable of detecting low-frequency variants, including OLA, may guide clinicians to prescribe more effective ART.